An Exploration of the Impact of Bilingualism on Mobility, Employability, and Intercultural Competence: The Colombian Case - Arnaiz-Castro, Patricia; Gómez-Parra, Mª Elena; Espejo-Mohedano, Roberto (Studia Anglica Posnaniensia, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*373.98px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.921619);" role="presentation">Research on bilingual education has looked <span dir="ltr" style="left: calc(var(--scale-factor)*278.09px); top: calc(var(--scale-factor)*373.98px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.970286);" role="presentation">mainly <span dir="ltr" style="left: calc(var(--scale-factor)*304.85px); top: calc(var(--scale-factor)*373.98px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.933224);" role="presentation">at the benefits bilingual programs <span dir="ltr" style="left: calc(var(--scale-factor)*426.79px); top: calc(var(--scale-factor)*373.98px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00655);" role="presentation">offer <span dir="ltr" style="left: calc(var(--scale-factor)*446.38px); top: calc(var(--scale-factor)*373.98px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.894623);" role="presentation">learners <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*384.78px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02256);" role="presentation">with regard to <span dir="ltr" style="left: calc(var(--scale-factor)*178.70px); top: calc(var(--scale-factor)*384.78px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.970465);" role="presentation">cognition, education, <span dir="ltr" style="left: calc(var(--scale-factor)*260.21px); top: calc(var(--scale-factor)*384.78px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.943846);" role="presentation">and language. <span dir="ltr" style="left: calc(var(--scale-factor)*315.89px); top: calc(var(--scale-factor)*384.78px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.906951);" role="presentation">Fewer <span dir="ltr" style="left: calc(var(--scale-factor)*342.31px); top: calc(var(--scale-factor)*384.78px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.937388);" role="presentation">studies ha<span dir="ltr" style="left: calc(var(--scale-factor)*379.99px); top: calc(var(--scale-factor)*384.78px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.937333);" role="presentation">ve <span dir="ltr" style="left: calc(var(--scale-factor)*392.47px); top: calc(var(--scale-factor)*384.78px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01689);" role="presentation">explored the effect of <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*395.58px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.04696);" role="presentation">bilingualism on mobility, employabilit<span dir="ltr" style="left: calc(var(--scale-factor)*266.57px); top: calc(var(--scale-factor)*395.58px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0081);" role="presentation">y, and intercultural competence, and even fewer have <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*406.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.91579);" role="presentation">centered on these th<span dir="ltr" style="left: calc(var(--scale-factor)*193.73px); top: calc(var(--scale-factor)*406.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.945154);" role="presentation">ree dimensions at once. Considering the wide range of skills <span dir="ltr" style="left: calc(var(--scale-factor)*417.31px); top: calc(var(--scale-factor)*406.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.945283);" role="presentation">required <span dir="ltr" style="left: calc(var(--scale-factor)*450.10px); top: calc(var(--scale-factor)*406.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.941591);" role="presentation">to be a <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*417.20px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.94375);" role="presentation">21<span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*417.20px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.830833);" role="presentation">st-<span dir="ltr" style="left: calc(var(--scale-factor)*138.62px); top: calc(var(--scale-factor)*417.20px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.966107);" role="presentation">century global citizen, <span dir="ltr" style="left: calc(var(--scale-factor)*222.65px); top: calc(var(--scale-factor)*417.20px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.04455);" role="presentation">it is <span dir="ltr" style="left: calc(var(--scale-factor)*239.21px); top: calc(var(--scale-factor)*417.20px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.963922);" role="presentation">crucial to achieve a more balanced portrait of bilingualism. <span dir="ltr" style="left: calc(var(--scale-factor)*458.86px); top: calc(var(--scale-factor)*417.20px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.949821);" role="presentation">This <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*428.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.953702);" role="presentation">study, part of a large-<span dir="ltr" style="left: calc(var(--scale-factor)*198.53px); top: calc(var(--scale-factor)*428.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.886016);" role="presentation">scale research project, seeks <span dir="ltr" style="left: calc(var(--scale-factor)*303.17px); top: calc(var(--scale-factor)*428.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.959);" role="presentation">to contribute to expandi<span dir="ltr" style="left: calc(var(--scale-factor)*389.59px); top: calc(var(--scale-factor)*428.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.926667);" role="presentation">ng the body of research <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*438.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.945);" role="presentation">that examines <span dir="ltr" style="left: calc(var(--scale-factor)*176.54px); top: calc(var(--scale-factor)*438.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.04091);" role="presentation">mobility, employabilit<span dir="ltr" style="left: calc(var(--scale-factor)*259.13px); top: calc(var(--scale-factor)*438.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.983688);" role="presentation">y, and intercultural competence <span dir="ltr" style="left: calc(var(--scale-factor)*382.75px); top: calc(var(--scale-factor)*438.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.927736);" role="presentation">together. <span dir="ltr" style="left: calc(var(--scale-factor)*418.87px); top: calc(var(--scale-factor)*438.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.14214);" role="presentation">A total of <span dir="ltr" style="left: calc(var(--scale-factor)*461.50px); top: calc(var(--scale-factor)*438.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.936875);" role="presentation">417 <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*449.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.9354);" role="presentation">participants <span dir="ltr" style="left: calc(var(--scale-factor)*165.14px); top: calc(var(--scale-factor)*449.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00603);" role="presentation">living in Colombia filled out an online <span dir="ltr" style="left: calc(var(--scale-factor)*307.85px); top: calc(var(--scale-factor)*449.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.941038);" role="presentation">fourteen-<span dir="ltr" style="left: calc(var(--scale-factor)*340.87px); top: calc(var(--scale-factor)*449.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.951964);" role="presentation">item <span dir="ltr" style="left: calc(var(--scale-factor)*359.23px); top: calc(var(--scale-factor)*449.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.93069);" role="presentation">questionnaire <span dir="ltr" style="left: calc(var(--scale-factor)*410.35px); top: calc(var(--scale-factor)*449.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.927543);" role="presentation">and a background <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*460.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.930862);" role="presentation">questionnaire <span dir="ltr" style="left: calc(var(--scale-factor)*172.82px); top: calc(var(--scale-factor)*460.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.903051);" role="presentation">designed <span dir="ltr" style="left: calc(var(--scale-factor)*208.73px); top: calc(var(--scale-factor)*460.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.01615);" role="presentation">by the <span dir="ltr" style="left: calc(var(--scale-factor)*236.33px); top: calc(var(--scale-factor)*460.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.933418);" role="presentation">members of <span dir="ltr" style="left: calc(var(--scale-factor)*284.33px); top: calc(var(--scale-factor)*460.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.9225);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*299.21px); top: calc(var(--scale-factor)*460.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.85681);" role="presentation">research <span dir="ltr" style="left: calc(var(--scale-factor)*332.95px); top: calc(var(--scale-factor)*460.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.94875);" role="presentation">project <span dir="ltr" style="left: calc(var(--scale-factor)*361.87px); top: calc(var(--scale-factor)*460.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.96619);" role="presentation">EDU2017-<span dir="ltr" style="left: calc(var(--scale-factor)*401.47px); top: calc(var(--scale-factor)*460.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.93675);" role="presentation">84800-R. <span dir="ltr" style="left: calc(var(--scale-factor)*439.03px); top: calc(var(--scale-factor)*460.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.877941);" role="presentation">Spearman <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*471.20px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.930662);" role="presentation">correlations were computed between the three dimensions and a strong interrelation was revealed <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*482.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.925307);" role="presentation">among the three of them. <span dir="ltr" style="left: calc(var(--scale-factor)*213.53px); top: calc(var(--scale-factor)*482.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.925025);" role="presentation">Data were analysed in terms of <span dir="ltr" style="left: calc(var(--scale-factor)*328.03px); top: calc(var(--scale-factor)*482.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.9225);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*341.47px); top: calc(var(--scale-factor)*482.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.916374);" role="presentation">differences between <span dir="ltr" style="left: calc(var(--scale-factor)*415.99px); top: calc(var(--scale-factor)*482.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.990758);" role="presentation">former bilingual <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*492.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.921449);" role="presentation">education learne<span dir="ltr" style="left: calc(var(--scale-factor)*179.66px); top: calc(var(--scale-factor)*492.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.887014);" role="presentation">rs and mainstream learners as well as across gender. <span dir="ltr" style="left: calc(var(--scale-factor)*368.23px); top: calc(var(--scale-factor)*492.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.90913);" role="presentation">Statistical analyses revealed a <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*503.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.934415);" role="presentation">strong interrelation among the three dimensions and higher scores for former bilinguals in all three <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*514.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.936928);" role="presentation">dimensions. No differences across gender were identified. The findings <span dir="ltr" style="left: calc(var(--scale-factor)*381.19px); top: calc(var(--scale-factor)*514.40px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.952774);" role="presentation">support the crucial role of <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*525.20px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.926774);" role="presentation">bilingual education in fostering the development of these three aspects in students’ perception. The <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*536.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.997538);" role="presentation">originality of the study lies in the fact that the study has former <span dir="ltr" style="left: calc(var(--scale-factor)*362.35px); top: calc(var(--scale-factor)*536.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02923);" role="presentation">bilingual <span dir="ltr" style="left: calc(var(--scale-factor)*397.63px); top: calc(var(--scale-factor)*536.00px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.921107);" role="presentation">education learners as <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*546.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.917373);" role="presentation">participants instead of st<span dir="ltr" style="left: calc(var(--scale-factor)*207.41px); top: calc(var(--scale-factor)*546.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.9102);" role="presentation">udents who <span dir="ltr" style="left: calc(var(--scale-factor)*250.37px); top: calc(var(--scale-factor)*546.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.933511);" role="presentation">were in <span dir="ltr" style="left: calc(var(--scale-factor)*278.81px); top: calc(var(--scale-factor)*546.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.905156);" role="presentation">recei<span dir="ltr" style="left: calc(var(--scale-factor)*296.21px); top: calc(var(--scale-factor)*546.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.985179);" role="presentation">pt of <span dir="ltr" style="left: calc(var(--scale-factor)*314.69px); top: calc(var(--scale-factor)*546.80px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.946755);" role="presentation">bilingual education at the time of completing <span dir="ltr" style="left: calc(var(--scale-factor)*120.50px); top: calc(var(--scale-factor)*557.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.936497);" role="presentation">the questionnaire, which <span dir="ltr" style="left: calc(var(--scale-factor)*211.13px); top: calc(var(--scale-factor)*557.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.895625);" role="presentation">had <span dir="ltr" style="left: calc(var(--scale-factor)*226.37px); top: calc(var(--scale-factor)*557.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.961333);" role="presentation">usually <span dir="ltr" style="left: calc(var(--scale-factor)*254.45px); top: calc(var(--scale-factor)*557.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.884063);" role="presentation">been <span dir="ltr" style="left: calc(var(--scale-factor)*273.77px); top: calc(var(--scale-factor)*557.60px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.906243);" role="presentation">the case in previous studies.